Pengaruh Struktur Modal, Pertumbuhan Perusahaan, Ukuran Perusahaan Terhadap Profitabilitas dan Nilai Perusahaan yang Terdaftar di Bursa Efek Indonesia - Bernon Sampe Tondok; Cepi Pahlevi; Andi Aswan (Hasanuddin Journal of Business Strategy, 2019)
This study examines the effect of capital structure, company growth, company size on profitability and company value the cases of manufacturing companies listed on the Indonesia Stock Exchange. This research is quantitative descriptive research using path analysis. Classical assumption evaluations are conducted comprising of normality, linearity, autocorrelation, multicollinearity, and heteroscedasticity test. The sample is 33 manufacturing companies listed on the Indonesia Stock Exchange from period 2013 – 2017. The results of the study found that there was a positive impact of capital structure, company growth, firm size on profitability and value of manufacturing companies.